Behavioral regulatory problems are associated with a lower attentional bias to fearful faces during infancy - Eskola Eeva; Kataja Eeva‐Leena; Hyönä Jukka; Häikiö Tuomo; Pelto Juho; Karlsson Hasse; Karlsson Linnea; Korja Riikka (Wiley, 2022)
To investigate the role of early regulatory problems (RP), such as problems in feeding, sleeping, and calming down during later development, the association between parent‐reported RP at 3 months (no‐RP, n = 110; RP, n = 66) and attention to emotional faces at 8 months was studied. Eight‐month‐old infants had a strong tendency to look at faces and to specifically fearful faces, and the individual variance in this tendency was assessed with eye tracking using a face‐distractor paradigm. The early RPs were related to a lower attention bias to fearful faces compared to happy and neutral faces after controlling for temperamental negative affectivity. This suggests that early RPs are related to the processing of emotional information later during infancy.